PERTUMBUHAN AKAR KECAMBAH KACANG HIJAU (Phaseolus radiatus L.) DI BAWAH PENGARUH MEDAN MAGNET - Taufik Ardiyanto; Rochmah Agustrina; Rini Rita T Marpaung (Universitas Lampung, 2014)
The purpose of this study was to determine the effect of long exposure of 0.1 mT magnetic field to root length of mung bean sprouts and the results of the research are used as material for making student’s worksheets. Research compiled in acompletely randomized design (CRD) with one factor that is a long exposure of 0.1mT magnetic field consisting of control (0 min), 7'48